Molecular Cytogenetics Of Myelodysplastic Syndrome – Hospital Based Study - Isa, Asmida (2014)
Myelodysplastic Syndrome (MDS) is a haematological condition characterised by hypercellular bone marrow and low peripheral blood counts. The objectives of this study were to identify chromosomal aberration using conventional cytogenetics and array comparative genomic hybridisation (array-CGH) in MDS patients and correlate with its’ haematological findings. A total of 8 patients were recruited. Cytogenetic mresults revealed six normal karyotypes, a karyotype with structural abnormalities (del(5)(q13q33) and a karyotype with complex rearrangement (t(1;11), t(2;11), del(4p), del(5p), del(9p)). By array-CGH technique, known cytogenetic aberrations, complex chromosome aberrations and rare/cryptic aberrations (<5 Mb) were detected.